A survey of tragic love in vocal repertoire for the lyric soprano - Luczak, Jessica (Kansas State University, 2013)
This report contains biographical, historical, and analytical commentary on the following composers and their pieces for soprano voice: Henry Purcell and The Blessed Virgin's Expostulation; Franz Schubert and Gesänge aus Wilhelm Meister, Op. 62, D. 877; Jacques Offenbach and Les oiseaux dans la charmille, from Les Contes d'Hoffmann; Libby Larsen and Try Me, Good King: Last Words of the Wives of Henry VIII; Charles Gounod and Ah! Je veux vivre, from Roméo et Juliette. These selections, unified by the theme of tragedy in various forms of love, were presented in a graduate recital in partial fulfillment of the requirements for the Master of Music in Vocal Performance and Pedagogy degree.
Keywords: Henry Purcell; Franz Schubert; Jacques Offenbach; Libby Larsen; Charles Gounod; Soprano voice recital; Fine Arts (0357); Music (0413); Musical Performances (0943); Pedagogy (0456); Performing Arts (0641)